Nonlinear Flame Dynamics for Laminar Flame in a Co-flow Mixing Layer with Widely Varying Premixedness: Preferential Diffusion and Stoichiometry Effects. Issue 7 (19th May 2022) - Bhatt, D.; Chakravarthy, S. R.
ABSTRACT: Intrinsic oscillations arising due to thermo-diffusive mechanism have been studied numerically in the literature for laminar flames having Lewis number greater than unity. In the previous work, the Lewis numbers of fuel and oxidizer are assumed to be equal and the unburnt mixture to be in stoichiometric in proportion. Here, the study is extended to relax these assumptions. In the first part of the present work, the Lewis numbers of fuel and oxidizer are varied individually keeping the overall mixture stoichiometric. The simulations are run for laminar flames stabilized near to a cold burner in a co-flow mixing layer generated by a fuel rich stream and oxidizer rich stream. The premixedness of the unburnt mixture is varied using a premixedness parameter defined in the previous work. This parameter characterizes upstream mixture-fraction gradients such that it approaches unity for zero mixture-fraction gradient and zero when the mixture-fraction gradient is infinite. Thus, upon ignition, different flame structures like, planar premixed flame, triple flames and an edge flame can be observed, as this parameter is varied from zero to unity. Simulations are run to study large time behavior for various values in this range of premixedness. Intrinsic oscillations in the total reaction rate (integrated over the domain) are observed for a combination of values of Lewis numbers of fuel and oxidizer. These are presented as series of contour plots of amplitude of total reaction rate onto a 2D plane with Lewis number of fuel on x -axis and Lewis number of oxidizer on y -axis for various values of premixedness. It is found that the contours of constant amplitude are nearly linear for diffusion flame and partially premixed flames, thus validating the effective Lewis number definition hitherto defined for diffusion flames. Hence, this effective Lewis number can determine the onset of oscillations and also their magnitude. But for weakly curved triple flames, there is significant variation, where the constant amplitude lines are curved. Also, the amplitude of oscillations observed for weakly curved triple flames is much higher than that for other flames. Apart from intrinsic oscillations the shape and structure of triple flame is also studied. It is found that premixed flame branches of a triple flame are highly asymmetric about the trailing edge diffusion flame. The change in the location of triple point is also observed. In the second part of the work, the assumption of the overall stoichiometric ratio being unity is relaxed to understand the effect of the off-stoichiometric mixture on the shape and stability of flame. However, the Lewis numbers of the fuel and oxidizer are maintained to be equal. The maximum intensity of oscillations is observed at an equivalence ratio of 0.3 for partially premixed flames and at around unity for premixed flames.